Wave attenuation characteristics of a wave suppress system - Teh, Hee Min (2006)
A floating breakwater named Wave Suppress System (WSS-GEN-1) was previously developed to arrest the destructive power of water waves. It was experimentally proven to be an effective energy dissipater for scattering the energy of prevailing waves mainly through breaking, turbulence and friction; however, it was not a good reflector. The present study aimed at improving the reflective characteristics of the existing floating breakwater system (GEN-1) and to experimentally study the wave attenuation performance of the improved WSS. Two major feature enhancements were applied to GEN-1: (i) 45o-slanting legs of the floating module; and (ii) keel plates beneath the module. Three WSS models, namely GEN-1, GEN-2 and GEN-2 with keel plates were constructed and the wave attenuation performance of the models was experimentally studied through a series of laboratory tests conducted in a wave flume. This paper addressed the performance of the tested WSS models in the form of coefficients of transmission, reflection and energy loss with respect to various wave environments. The test results showed that the WSS models were generally effective energy dissipaters. The reflective characteristics of GEN-1 were successfully enhanced by increment of freeboard and slanting bottom feature in GEN-2. The wave reflection performance was further enhanced as the draft of the GEN-2 model was extended via keel plates, and consequently retarding wave transmission significantly.